2012
DOI: 10.4103/0972-2327.104334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of augmented proprioceptive cues on the parameters of gait of individuals with Parkinson′s disease

Abstract: Context:Impairment of initiating sequential movements and processing of proprioception contribute to characteristic Parkinson's disease (PD) gait abnormalities. Many studies have used a single external cue or 2 different cues to correct PD gait.Aim:An aim of this study was to determine the influence of paired proprioceptive cues on gait parameters of individuals with PD.Setting and Design:Double-blind randomized controlled trial.Materials and Methods:Subjects were 30 PD patients who had mild to moderate impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…80 In contrast, 2 high-quality studies were negative; 1 using an avatar versus conventional balance training for balance 81 and 1 evaluating robotic gait training versus balance training. 82,83 Other technologies that were evaluated included the use of a Nintendo Wii versus balance exercises, 84 smartphone biofeedback 85 and a gamepad-"dancing software," 86 vibratory devices added to shoes 87 with overall positive outcomes in both groups, but all were lower quality studies. Studies in which there was no active intervention and where participants received the usual medical therapy as a comparator or where there was unclear final statistical analysis were all lowquality, and therefore the interpretations of outcome conclusions were limited.…”
Section: New Conclusion For Adjunct Therapies For Specific or Generamentioning
confidence: 99%
“…80 In contrast, 2 high-quality studies were negative; 1 using an avatar versus conventional balance training for balance 81 and 1 evaluating robotic gait training versus balance training. 82,83 Other technologies that were evaluated included the use of a Nintendo Wii versus balance exercises, 84 smartphone biofeedback 85 and a gamepad-"dancing software," 86 vibratory devices added to shoes 87 with overall positive outcomes in both groups, but all were lower quality studies. Studies in which there was no active intervention and where participants received the usual medical therapy as a comparator or where there was unclear final statistical analysis were all lowquality, and therefore the interpretations of outcome conclusions were limited.…”
Section: New Conclusion For Adjunct Therapies For Specific or Generamentioning
confidence: 99%
“…2021 Moreover, one study found that proprioceptive feedback exercises improved walking speed in individuals with Parkinson’s disease, suggesting the importance of proprioceptive inputs to gait function. 22 We adjusted for both visual acuity and monofilament testing in our regression models and did not observe that these factors explained the association between static balance and walking speed. However, vision loss and proprioceptive impairment are multifaceted, and also involve contrast sensitivity, visual fields, and depth perception in the case of vision and joint and muscle proprioception in the case of proprioception.…”
Section: Discussionmentioning
confidence: 95%
“…The first treatment proposed was Rhythmic Cues, as auditory and visual rhythmic cues are effective in improving the gait of individuals with PD; these improve step preparation (12) due to the greater attention demanded during the task (13). Studies reveal that rhythmic cues help PD patients to replace typical automatic gait control with a more conscious and perhaps, more discreet movement, making walking easier.…”
Section: Introductionmentioning
confidence: 99%